1991
DOI: 10.4141/cjas91-021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the quality of ground water supplies used on Saskatchewan swine farms

Abstract: An extensive survey of well water used on swine farms in Saskatchewan was undertaken as a first step in trying to clarify the apparent disagreement between field and laboratory observations with respect to water quality and pig performance. One hundred and thirty-five wells throughout the province were sampled for a comprehensive chemical analysis; at the same time, a questionnaire concerning pig performance and perceptions of water quality was administered to the well owners. Concentrations of sulphate and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Scours (diarrhea) are commonly used as an indicator of compromised health status in weanling pigs. Thus, a negative water balance is associated with the presence of scours and commonly occurs in young pigs, as the balance of water within the pig can be interrupted during times of health challenges (Brooks et al, 1984;Stockill, 1990;McLeese et al, 1991). Ultimately, water balance in the pig can be disrupted by any event or process that causes excretion of water to exceed intake of water, resulting in compromised performance and health of pigs.…”
Section: Factors Affecting Water Intake and Usage By Pigsmentioning
confidence: 99%
“…Scours (diarrhea) are commonly used as an indicator of compromised health status in weanling pigs. Thus, a negative water balance is associated with the presence of scours and commonly occurs in young pigs, as the balance of water within the pig can be interrupted during times of health challenges (Brooks et al, 1984;Stockill, 1990;McLeese et al, 1991). Ultimately, water balance in the pig can be disrupted by any event or process that causes excretion of water to exceed intake of water, resulting in compromised performance and health of pigs.…”
Section: Factors Affecting Water Intake and Usage By Pigsmentioning
confidence: 99%
“…The most common dis-solved salts contaminating well water throughout North America are sulfates. A survey conducted by McLeese et al (1991) indicated that over 25% of wells in Saskatchewan used for swine production have concentrations greater than 1,000 mg/L. Another survey in Ohio (Veenhuizen, 1993) concluded that wells ranged in concentrations of 6 to 1,629 mg/L sulfate.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water can contribute significantly to sulphur intake of pigs. One major source is the sulphate content in water supplies, which has been found to exceed 1600 mg/L in certain geographic areas (McLeese et al, 1991;Veenhuizen, 1993). Studies showed that pigs offered water with increased sulphate levels (up to 1800 mg/L) had increased prevalence of nonpathogenic diarrhea (Veenhuizen et al, 1992).…”
Section: Introductionmentioning
confidence: 99%